Anticancer and Cytotoxicity Activity of Native and Modified Black Rice Flour on Colon Cancer Cell Lines. (21st February 2022) - Thanuja, B.; Parimalavalli, R.; Vijayanand, S.; Alharbi, Reem Mohammed; Abdel-Raouf, Neveen; Ibraheem, Ibraheem Borie M.; Sholkamy, Essam Nageh; Durairaj, Kaliannan; Meansbo Hadish, Kibrom
Abstract : This study is intended to evaluate the cytotoxicity of native and dual-modified black rice flour against the colon cancer cell line (HCT116) and mouse embryo cell line (3T3-L1) by using the MTT assay. The modification techniques applied to prepare rice flour samples were enzymatic modification and heat moisture treatment. In this study, the IC50 of native black rice flour and modified black rice flour was 255.78 µ g/mL and 340.85 µ g/mL, respectively. The result confirms that the native black rice flour has significant cytotoxic and anticancer potential against human colon cancer cells. In addition, the IC50 of native black rice flour and modified black rice flour on the 3T3-L1 cell line was found to be 345.96 µ g/mL and 1106.94 µ g/mL, respectively. The results showed that the native black rice flour had weak cytotoxicity, and modified black rice flour was nontoxic in both the cell lines. The active component of phytochemicals present in black rice flour has a potential role in preventing colon cancer.